Targeted/exome sequencing identified mutations in ten Chinese patients diagnosed with Noonan syndrome and related disorders - Shanshan Xu; Yanjie Fan; Yu Sun; Lili Wang; Xuefan Gu; Yongguo Yu (BMC, 2017)
Abstract Background Noonan syndrome (NS) and Noonan syndrome with multiple lentigines (NSML) are autosomal dominant developmental disorders. NS and NSML are caused by abnormalities in genes that encode proteins related to the RAS-MAPK pathway, including PTPN11, RAF1, BRAF, and MAP2K. In this study, we diagnosed ten NS or NSML patients via targeted sequencing or whole exome sequencing (TS/WES). Methods TS/WES was performed to identify mutations in ten Chinese patients who exhibited the following manifestations: potential facial dysmorphisms, short stature, congenital heart defects, and developmental delay. Sanger sequencing was used to confirm the suspected pathological variants in the patients and their family members. Results TS/WES revealed three mutations in the PTPN11 gene, three mutations in RAF1 gene, and four mutations in BRAF gene in the NS and NSML patients who were previously diagnosed based on the abovementioned clinical features. All the identified mutations were determined to be de novo mutations. However, two patients who carried the same mutation in the RAF1 gene presented different clinical features. One patient with multiple lentigines was diagnosed with NSML, while the other patient without lentigines was diagnosed with NS. In addition, a patient who carried a hotspot mutation in the BRAF gene was diagnosed with NS instead of cardiofaciocutaneous syndrome (CFCS). Conclusions TS/WES has emerged as a useful tool for definitive diagnosis and accurate genetic counseling of atypical cases. In this study, we analyzed ten Chinese patients diagnosed with NS and related disorders and identified their correspondingPTPN11, RAF1, and BRAF mutations. Among the target genes, BRAF showed the same degree of correlation with NS incidence as that of PTPN11 or RAF1.